Thermo-Hydromechanical Coupling Responses Driven by a Central Heat Source in Unsaturated Soils - Wei Wang; Jingjing Liu; Jing Chen (Advances in Materials Science and Engineering)
Based on the thermodynamic and thermoelastic theory, the coupled governing equations of deformation, heat transfer, and moisture migration in unsaturated soils were given. The coupled calculation process was realized by the finite element method. The hydrothermal coupling characteristics of two cases of unsaturated kaolin clay were studied by using a self-developed test device, and the test results were compared with the numerical results. The results showed that when the initial saturation of the soil is high, the volumetric water content of the measured point increases, and then it is in a stable state during the heating process. When the initial saturation is low, the volumetric water content near the heat source increases firstly and then decreases during the heating process. The rise and fall of temperature make the volumetric water content of the soil irreversible. The volumetric water content of each measured point is lower than the initial state. The closer it is to the internal measured heat source, the more obvious this phenomenon is; the lower the initial saturation is, the more obvious it is.